2014
DOI: 10.5946/ce.2014.47.2.188
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Duodenal Perforation Caused by a Lollipop Stick: A Case Report

Abstract: Most ingested foreign bodies often pass through the gastrointestinal tract uneventfully; however, complications such as perforation do occur. Most cases of perforation are caused by thin, pointed objects such as needles, toothpicks, or fish and chicken bones. Herein, we report an unusual case of duodenal perforation caused by a lollipop stick with blunt ends. A 23-year-old woman was admitted to the emergency department complaining of epigastric and right upper quadrant pain for the last 2 days. Abdominal compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…An orally ingested object passes through the oropharynx, pharynx, esophagus, cardia, pylorus, duodenum, small intestine, and colon, sometimes leading to obstruction and perforation at the anorectal level before penetrating into the rectoanal region. [5,[7][8][9] Objects smaller than 6 cm and those with a structure thinner than 2 cm require no intervention and are naturally discharged. [5] In some cases, the ingested object remains in the body with no symptoms, and leads to unexpected complication after a long period.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An orally ingested object passes through the oropharynx, pharynx, esophagus, cardia, pylorus, duodenum, small intestine, and colon, sometimes leading to obstruction and perforation at the anorectal level before penetrating into the rectoanal region. [5,[7][8][9] Objects smaller than 6 cm and those with a structure thinner than 2 cm require no intervention and are naturally discharged. [5] In some cases, the ingested object remains in the body with no symptoms, and leads to unexpected complication after a long period.…”
Section: Discussionmentioning
confidence: 99%
“…[5,[7][8][9] Objects smaller than 6 cm and those with a structure thinner than 2 cm require no intervention and are naturally discharged. [5] In some cases, the ingested object remains in the body with no symptoms, and leads to unexpected complication after a long period. Misra et al suggested that conservative treatment of asymptomatic cases is ideal, and that intervention should be performed following onset of first symptom.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations